Effect of surface treatments and thermocycling on shear bond strength of various artificial teeth with different denture base materials - Hikmat J Aljudy; Ali N Hussein; Ihab N Safi (College of Dentistry/ University of Baghdad, 2014)
Background: Separation and deboning of artificial teeth from denture bases present a major clinical and labortory problem which affect both the patient and the dentist. The optimal bond strength of artificial teeth with denture base reinforced with nanofillers and flexible denture bases and the effect of thermo cycling should be evaluated. This study was conducted to evaluate and compare the shear bond strength of artificial teeth (acrylic and porcelain) with denture bases reinforced by 5% Zirconium oxide nanofillers and flexible bases under the effect of different surface treatments and thermo cycling and comparing the results with conventional water bath cured denture bases. Material and methods: Two types of artificial teeth; acrylic and porcelain were used and prepared for this study. Five specimens of each tooth type were processed to each denture base materials after the application of different surface treatments; these teeth were bonded to heat polymerized, nano composite resin and flexible denture bases. Specimens were thermo cycled and tested for bond strength until fracture with an Instron universal testing machine. Data were analyzed with analysis of variance and student T-test. Photomicrographic examinations were used to identify adhesive and cohesive failures within debonded specimens. Results: The mean force required to fracture the specimens were obviously larger for nanocomposite specimens compared with the heat cured and flexible specimens. The most common failure was cohesive within the tooth or the denture base. With each base material, the artificial teeth which were treated with thinner exhibited highest shear bond strength. Thermocycling had deleterious effect on the flexible denture base specimens. In general, nanocomposite and heat cured groups failed cohesively within the artificial tooth. While the valplastic groups failed adhesively at the tooth denture base interface. Conclusions: Within the limitations of this study, the type of denture base materials and surface treatments of the tooth selected for use may influence the shear bond strength of the tooth to the base. Selection of more compatible combinations of base and artificial teeth may reduce the number of prosthesis fractures and resultant repairs. Key words: acrylic teeth, porcelain teeth, Nano composite denture base, thermo cycling, flexible denture, thinner,